Quantifying the 'Gorilla Arm' Effect in a Virtual Reality Text Entry Task via Ray-Casting: A Preliminary Single-Subject Study - Palmeira, Eduardo G. Q.; Campos, Alexandre; Moraes, Ígor A.; de Siqueira, Alexandre G.; Ferreira, Marcelo G. G. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2023: Anais do XXV Simpósio de Realidade Virtual e Aumentada, 2023)
Inputting text is a fundamental task users perform in immersive virtual reality (VR) environments. This preliminary study quantifies the ‘gorilla arm’ effect regarding the required torque in the upper limb joints of an individual during a VR text entry task via raycasting. This type of fatigue can be caused by the weight of the users’ arms, depending on the arm pose maintained during a task. We used motion capture technology to compare the required arm joints’ torque in two typical arm poses during VR text entry tasks. The results suggest that extending the arm higher and in front of the body towards the virtual keyboard causes about 3.77 times more net torque on the shoulder joint and 2.00 times more on the elbow joint, compared to when the arm is in a more relaxed and lowered position. These findings can support future VR text entry studies concerned with physical ergonomics.